Fruit characterization and genetic diversity among tamarind matrices - Rodrigues Gomes, Francielly; Lopes Barros, Ângela; Gomes Machado, Carla; Carlos Silva Cruz, Simério Carlos; Hurtado Salazar, Alejandro; Pereira da Silva, Danielle Fabíola (Revista Ceres, 2025)
Tamarind is a tropical fruit highly cultivated in some countries. In Brazil, still there is a little exploitation of tamarind fruits, but its characterization can subsidize the commercial exploitation. Fruit characterization enables the study of genetic diversity between matrices or populations, allowing the identification of possible genitors, or even genotypes with superior characteristics. The aim of this study was to characterize and evaluate the genetic diversity of the physical characteristics of tamarind fruit, in order to provide subsidies for genetic improvement programs and conservation of the species. The fruits were evaluated by weight, diameter and length, color of epidermis and pulp. A completely randomized design was adopted, with 4 treatments (plants) and 7 replicates of 10 fruits, totaling 280 fruits. The data were subjected to analysis of variance, and the means were compared using the Duncan test. The matrix 4 presented higher values of weight, length and diameter, when compared to the others. There is genetic diversity among the tamarind matrices. Two groups were formed using the dendrogram generated by the UPGMA method. A strong correlation was observed between fruit length and weight, peel weight and fruit weight, and peel weight and length, which is crucial information for genetic improvement.